Zmienność genetyczna naturalnego odnowienia i drzewostanu macierzystego sosny (Pinus sylvestris L.) i świerka (Picea abies L. Karst.) - Nowakowska, Justyna; Konecka, Agata; Zachara, Tadeusz (Leśne Prace Badawcze, 2014)
The genetic variability and biodiversity of tree populations ensures the stability and sustainability of forest ecosystems. New research tools based on molecular DNA markers enable precise characterization of forest genetic resources, i.e. detection of different allele frequencies in mature trees and progeny populations. The paper describes the genetic structure of mature stands of Scots pine ( Pinus sylvestris L.) in Oława Forest District, and Norway spruce ( Picea abies L. Karst.) in Jawor Forest District and stands of their respective progeny. In the Scots pine stand, there was a slight increase (0.6%) in heterozygosity level and alarger increase (4.9%) in the inbreeding coefficient of progeny trees. In the Norway spruce stand, despite a small reduction (0.9%) in heterozygosity, a similar increase (4.6%) in the inbreeding coefficient of progeny was revealed. In both stands, allele richness and the partition probability of basic clustering were high. Both pine and spruce adults and progeny trees were characterized by high levels of genetic similarity (96% and 79% respectively). Gene flow between the mature and progeny populations was high (Nm > 1) for both Scots pine and Norway spruce. Conservation of the gene pool within forest tree stands requires an increase in the proportion of natural regeneration. To estimate the extent to which genes are transmitted between adult trees and their progeny more studies are needed, especially taking into account the influence of silviculture measures, like selective tree cutting, on the genetic variability of the younger generation. These results confirm that the gene pool was conserved when transmitted between the stands studied, as well as highlighting the usefulness of such a study for the silvicultural purposes.